2019
DOI: 10.1111/cei.13251
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and regulatory CCL and CXCL chemokine and cytokine cellular responses in patients with patentMansonella perstansfilariasis

Abstract: Mansonella perstans (Mp) filariasis is present in large populations in sub-Saharan Africa, and to what extent patent Mp infection modulates the expression of immunity in patients, notably their cellular cytokine and chemokine response profile, remains not well known. We studied the spontaneous and inducible cellular production of chemokines (C-X-C motif) ligand 9 (CXCL9) [monokine induced by interferon (IFN)-γ (MIG)], CXCL-10 [inducible protein (IP)-10], chemokine (C-C motif) ligand 24 (CCL24) (eotaxin-2), CCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Analysis by one-way ANOVA test indicated significant differences among the different groups (*P < 0.05, **P < 0.01, ***P < 0.001 vs the control group. + P < 0.05, ++ P < 0.01, +++ P < 0.001 vs the CsTP+HBV group) ◂ or anti-inflammatory activities [38][39][40]. We previously revealed that CsTPs could promote the production of Th2 cytokines, including IL-13 and IL-4, both in vitro and in vivo, and ultimately resulted in the development of liver fibrosis [16].…”
Section: Discussionmentioning
confidence: 97%
“…Analysis by one-way ANOVA test indicated significant differences among the different groups (*P < 0.05, **P < 0.01, ***P < 0.001 vs the control group. + P < 0.05, ++ P < 0.01, +++ P < 0.001 vs the CsTP+HBV group) ◂ or anti-inflammatory activities [38][39][40]. We previously revealed that CsTPs could promote the production of Th2 cytokines, including IL-13 and IL-4, both in vitro and in vivo, and ultimately resulted in the development of liver fibrosis [16].…”
Section: Discussionmentioning
confidence: 97%
“…Although millions of humans are infected and suffer from severe pathology, knowledge about parasite evasion and survival tactics are not fully understood. Over the last decades, several studies showed that filariae modulate immunity in humans through the induction of Th2 and regulatory T and B cell populations accompanied with the suppression of pro-inflammatory and Th1 immune responses to guarantee long-term survival and reproduction of the parasite (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)63). Nevertheless, it is impossible to investigate the complexity of the filarial-driven modulation and survival tactics solely in humans due to limited access to parasitic life stages, unknown infection time point, possible re-and co-infections and most importantly ethical concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have characterized host immunity during filarial infections and revealed that filarial infections dampen and modulate host immune responses via the induction of regulatory B and T cell subsets, Th2 cell populations and distinct patterns of cytokines, chemokines and immunoglobulins accompanied with the suppression of Th1 and pro-inflammatory cell subsets (10)(11)(12)(13)(14)(15)(16)(17)(18). This immunomodulation leads in most infected people to an asymptomatic clinical picture which is essential for long-term survival of the parasites (19,20), but is also suggested to influence disease outcome of concomitant infections as well as vaccination efficacy (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…When this balance is disrupted, it may lead to an inflammatory response and cause a series of nerve injuries. [ 21 ] Zerbo et al demonstrated differential expression of MCP-1, RANTES, and MIP-1α in ASD. [ 22 ] In congruence with previous reports, our findings showed that compared with healthy children, those with ASD showed significantly increased MCP-1 levels ( P < .01) and significantly decreased MIP-1α and MIP-1β levels ( P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, IL-8 and IP-10 are in a dynamic balance. When this balance is disrupted, it may lead to an inflammatory response and cause a series of nerve injuries [21] . Zerbo et al demonstrated differential expression of MCP-1, RANTES, and MIP-1α in ASD [22] .…”
Section: Discussionmentioning
confidence: 99%